2015
DOI: 10.1111/pre.12084
|View full text |Cite
|
Sign up to set email alerts
|

Thalassiosira sundarbana sp. nov. (Bacillariophyta), an estuarine diatom from Sundarbans mangrove ecoregion based on morphology and molecular phylogeny

Abstract: A new species of diatom, Thalassiosira sundarbana, is described based on light and scanning electron microscopy along with molecular phylogeny. The specimen was collected from Chemaguri creek of the Indian part of Sundarbans mangroves, and subsequently a clonal culture was established. Thalassiosira sundarbana possess variable numbers of occluded processes, and one labiate process on the valve face. Valve margin is ribbed and areolae are fasciculated on the valve face. Two rings of strutted processes are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…On the eastern border of River Hooghly lies the largest island of the Indian Sundarbans, Sagar Island. Two predefined stations, Stn1 and Stn3, lie in Chemaguri creek and Mooriganga estuary respectively, and are part of the Sundarbans Biological Observatory Time Series (SBOTS) (Bhattacharjee et al 2013, Samanta and Bhadury 2015, Choudhury et al 2015. Chemaguri creek originates in the River Hooghly, transverses the island, and opens into the Mooriganga River.…”
Section: Study Sitementioning
confidence: 99%
“…On the eastern border of River Hooghly lies the largest island of the Indian Sundarbans, Sagar Island. Two predefined stations, Stn1 and Stn3, lie in Chemaguri creek and Mooriganga estuary respectively, and are part of the Sundarbans Biological Observatory Time Series (SBOTS) (Bhattacharjee et al 2013, Samanta and Bhadury 2015, Choudhury et al 2015. Chemaguri creek originates in the River Hooghly, transverses the island, and opens into the Mooriganga River.…”
Section: Study Sitementioning
confidence: 99%
“…Incidentally, T . sundarbana is a new species of Thalassiosira that has been recently discovered and described from an estuarine environment in Sundarbans ( Samanta and Bhadury, 2015 ). The detection of rbc L signatures of T. sundarbana additionally from SBR suggested that this species may be indigenous to Sundarbans mangrove and also has a broad distribution throughout the ecosystem.…”
Section: Resultsmentioning
confidence: 99%